Is It Important to Adapt Neoadjuvant Chemotherapy to the Visible Clinical Response? An Open Randomized Phase II Study Comparing Response-Guided and Standard Treatments in HER2-Negative Operable Breast Cancer. (30th January 2015) - Wang-Lopez, Qian; Mouret-Reynier, Marie-Ange; Savoye, Aude-Marie; Abrial, Catherine; Kwiatkowski, Fabrice; Garbar, Christian; DuBray-Longeras, Pascale; Eymard, Jean-Christophe; Lebouedec, Guillaume; Vanpraagh, Isabelle; Penault-Llorca, Frederique; Chollet, Philippe; et al.
Abstract: Author Summary: Background: Neoadjuvant treatment provides a unique opportunity to evaluate individual tumor sensitivity. This study evaluated whether a response-guided strategy could improve clinical outcome compared with a standard treatment. Methods: Overall, 264 previously untreated stage II–III operable breast cancer patients were randomized to receive either standard treatment (arm A, n = 131), consisting of fluorouracil, epirubicin, and cyclophosphamide (FEC100: 500, 100, and 500 mg/m 2, respectively, for 3 cycles) followed by docetaxel (100 mg/m 2 for 3 cycles), or adapted treatment (arm B, n = 133), beginning with 2 cycles of FEC100 and switching to docetaxel if tumor size decreased by <30% after 2 cycles or <50% after 4 cycles of FEC100 (ultrasound assessments according to World Health Organization criteria). Otherwise, FEC100 was given for six cycles before surgery. Intent-to-treat analysis was performed. Results: Similar results were observed for clinical response (objective response was 54% vs 56%, p = .18), breast conservation surgery (BCS; 67% vs 68%, p = .97), and pathological complete response rate (Chevallier classification: 14% vs 11%, p = .68; Statloff classification: 16% vs 13%, p = .82) between arms A and B. Similar toxicities were observed, even with unbalanced numbers of FEC100 and docetaxel courses. Conclusion: Adapted and standard treatments had similar results in terms of tumor response, BCS rate, and tolerability. Further survival outcome data are expected.